Sensitivity analysis of ground level ozone in India using WRF-CMAQ models. (April 2016) - Sharma, Sumit; Chatani, Satoru; Mahtta, Richa; Goel, Anju; Kumar, Atul
Abstract: Ground level ozone is emerging as a pollutant of concern in India. Limited surface monitoring data reveals that ozone concentrations are well above the prescribed national standards. This study aims to simulate the regional and urban scale ozone concentrations in India using WRF-CMAQ models. Sector-specific emission inventories are prepared for the ozone precursor species at a finer resolution (36 × 36 km 2 ) than used in previous studies. Meteorological fields developed using the WRF model are fed into the CMAQ model along with the precursor emissions to simulate ozone concentrations at a regional scale. The model is validated using observed ozone dataset. Sensitivity analysis is carried out to understand the effect of different precursor species and sources on prevailing ozone concentrations in India. The results show that NOx sensitive conditions prevail in India and control of NOx will result in more reduction in ozone than VOCs. However, further growth in the transport and power sector and decreasing VOC emissions from the residential sector may increase the sensitivity of VOCs towards ozone in the future. At the urban scale, presence of high NOx emissions form VOC limited conditions and reduction of NOx results in increase in ozone concentrations. However, this will help in improving regional scale ozone pollution in the downwind regions. A non-linear response has been observed while assessing the sectoral sensitivities of ozone formation. Transport sector is found to have the maximum potential for reducing ozone concentrations in India. Highlights: Modelling of Ozone concentrations using high resolution inventories in India. NOx sensitive conditions prevail in India. Transport sector have the maximum potential for reducing Ozone in India. At urban scale, reduction of NOx results in increase in Ozone concentrations. In future NMVOC sensitivities towards Ozone increase marginally.